Semirefined Carrageenan (SRC) Film Incorporated with α-Tocopherol and Persicaria minor for Meat Patties Application - Khadijah Husna, Abd Hamid; Wan Amnin, Wan Yahaya; Neenasha Bebe, Mohd Nor; Alyaa Syahierra, Ghazali; Siti Kholijah, Abdul Mudalip; Norashikin, Mat Zain; Almajano, María Pilar; Nurul Aini, Mohd Azman (Department of Chemistry, Universitas Gadjah Mada Yogyakarta, 2019)
Semirefined carrageenan (SRC) plasticized with glycerol (G) and incorporated with antioxidants of 0.4% (v/v) of α-tocopherol and Persicaria minor (PM) extract was successfully developed. The objective of this study is to analyze the antioxidant effect of active packaging films from semirefined carrageenan incorporated with α-tocopherol and Persicaria minor on meat patties. Total phenolic content and antioxidant activity of α-tocopherol and PM extract were measured. The effects of α-tocopherol and PM extract incorporated with SRC-based films on meat patties were evaluated using thiobarbituric acid reactive substance (TBARS) assay, metmyoglobin assay, and pH value for 14 days of storage. The films with 0.4% (v/v) of α-tocopherol and PM extract exhibited lower lipid oxidation in meat patties compared to the control (SRC film only, p < 0.05). Also, brown color development of the meat patties of less than 50% was observed at the end of the 14-day storage. Meanwhile, the pH values for all samples decreased throughout the storage period with the SRC+G+α-tocopherol film showed the highest pH value. Hence, the formulation of SRC film with α-tocopherol or PM extract could be used as an alternative packaging for extending the shelf life of food product with high fat content